Protease-Activated Receptor 2: Are Common Functions in Glial and Immune Cells Linked to Inflammation-Related CNS Disorders? - Bushell, Trevor J; Cunningham, Margaret R; McIntosh, Kathryn A; Moudio, Serge; Plevin, Robin (Current drug targets, 2016)
Protease-activated receptors (PARs) are a novel family of G-protein coupled receptors (GPCRs) whose activation requires the cleavage of the N-terminus by a serine protease. However, recent evidence reveals that alternative routes of activation also occur, that PARs signal via multiple pathways and that pathway activation is activator- dependent. Given our increased understanding of PAR function both under physiological and pathophysiological conditions, one aspect that has remained constant is the link between PAR2 and inflammation. PAR2 is expressed in immune cells of both the innate and adaptive immune system and has been shown to play a role in several peripheral inflammatory conditions. PAR2 is similarly expressed on astrocytes and microglia within the CNS and its activation is either protective or detrimental to CNS function depending on the conditions or disease state investigated. With a clear similarity between the function of PAR2 on both immune cells and CNS glial cells, here we have reviewed their roles in both these systems. We suggest that the recent development of novel PAR2 modulators, including those that show biased signalling, will further increase our understanding of PAR2 function and the development of potential therapeutics for CNS disorders in which inflammation is proposed to play a role.